2020
DOI: 10.5114/biolsport.2020.96318
|View full text |Cite
|
Sign up to set email alerts
|

Post-activation performance enhancement (PAPE) after a single-bout of high-intensity flywheel resistance training

Abstract: This study investigated the post-activation performance enhancements (PAPE) induced by a high-intensity single set of accentuated eccentric isoinertial resistance exercise on vertical jump performance. Twenty physically active male university students performed, in randomized counterbalanced order, two different conditioning activities (CA) after a general preestablished warm-up: a conditioning set of 6 maximum repetitions at high intensity (i.e., individualized optimal moment of inertia [0.083 ± 0.03 kg·m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
5
35
0
1
Order By: Relevance
“…The CMJ has specifically been used in PAPE studies investigating changes in lower body power production. The lack of differences in jump height performance after a CS found in this study are also found in others (2,24), although other studies showing a significant positive improvement (7,21,23). Similarly, studies that have also chosen to measure power output have seen mixed results, with some studies realizing increases in power output (7,21,23) and others not (2,24).…”
Section: Jump Performance and Post-activation Performance Enhancementsupporting
confidence: 75%
See 1 more Smart Citation
“…The CMJ has specifically been used in PAPE studies investigating changes in lower body power production. The lack of differences in jump height performance after a CS found in this study are also found in others (2,24), although other studies showing a significant positive improvement (7,21,23). Similarly, studies that have also chosen to measure power output have seen mixed results, with some studies realizing increases in power output (7,21,23) and others not (2,24).…”
Section: Jump Performance and Post-activation Performance Enhancementsupporting
confidence: 75%
“…These specific time points were chosen thoughtfully. The ideal time course between the CS and PAPE is still unclear with improvements identified immediately post-CS (10,12) to up to 20 minutes post-CS (21). Methodological factors such as type of CS and participant characteristics may play a role in the variability.…”
Section: Experimental Sessionmentioning
confidence: 99%
“…These improvements may be attributed to the SSC, typically involved during plyometric exercises, such as jumping [ 35 ]. A positive PAPE effect on the jumping performance has been reported when using FRTD [ 17 , 24 , 28 , 29 , 30 ]. Although we observed non-significant differences among protocols in the current study, the positive changes in CMJ ( d = 1.19—very large effect) performance in response to the FW conditioning exercise were comparable to those reported in the literature using FRTD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Maroto-Izquierdo et al [ 36 ] suggested that greater improvements in vertical jump performance were induced after the use of FRTD when compared with traditional resistance training. It seems that, when the recovery time was higher, a superior PAPE effect can be observed in the CMJ using both free weight [ 37 ] or FRTD [ 29 ]. This lack of significance could also be attributed to the moment of inertia used (i.e., external load or training intensity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation